Small Changes Counseling - William Billich; Igor Bussel; Jeffery Felgner; Daniela Berger; Sweta Narasimhan; Cathy Lazarus (Association of American Medical Colleges, 2014)
Abstract Introduction The Small Changes Counseling (SCC) curriculum is an educational module designed to enhance the health coaching ability of first- and second-year medical students. This module first teaches the principles of motivational interviewing (MI) before applying these skills to advise weight loss in a structured framework. This curriculum is minimal and efficiently covers key concepts necessary to advise behavioral modification. Methods The curriculum is administered in two phases. The first contains a series of self-instructed didactics where students learn the concepts of MI and a conversational model for counseling weight loss. The second phase involves a two-part practice counseling exercise. Students pair up to practice communication skills, then take turns counseling the facilitator, who plays the role of an overweight patient considering a lifestyle alteration. Results We performed a research study to assess the reception of the curriculum at Chicago Medical School at Rosalind Franklin University of Medicine & Science. The counseling exercise significantly affected the students' perspective of MI (p < .001) and counseling skills (p < .05). Additionally, 86.59% of the students recommended the inclusion of the SCC lab in future years. Fourth-year medical students and physicians who facilitated the mock counseling exercise unanimously supported the inclusion of SCC. Discussion These materials give students the important background on the topics of MI and weight loss behavioral counseling. What students discover in the counseling exercise, however, is that despite their best intentions, they often find themselves defaulting to directing patients as opposed to guiding. It is a useful teachable moment, as students become aware of their intrinsic desire to fix in their efforts to help. This humbling moment illustrates the subtle difficulty in becoming a skilled counselor.